Applying the SCAN methodology to the semiconductor supply chain - Paolo Bonnet; Andrea Ciani (European Commission, 2023)
The SCAN ("Supply Chain Alert Notification") methodology has been developed to report signs of distress in supply chains relying on trade data. This methodology is based on a set of structural indicators to assess the ex-ante systemic risk of disruptions, and on high-frequency indicators detecting price increases and/or sizeable reductions in traded volumes. The SCAN is here applied to a basket of 74 products traded in different segments of the semiconductor supply chain, from raw materials to the final products of the chain. We find that ten products belonging to the semiconductor supply chain can be considered in medium or high risk of import disruption due to high import concentration and low substitutability in year 2021. These products belong to various segments of the value chain: raw materials, inputs for the production of wafers, equipment for the manufacture of semiconductors, and semiconductor devices. According to the SCAN methodology, EU imports of six of these products can also be considered in high distress due to observed reductions in import quantities accompanied by increases in import prices in the last available quarter (Nov. 2022 - Jan. 2023).
Keywords: 330; Semiconductors; Supply Chains; Trade Data